Projecting the self into the future in individuals with schizophrenia: a preliminary cross-sectional study. Issue 6 (2nd July 2016) - Raffard, Stéphane; Bortolon, Catherine; D'Argembeau, Arnaud; Gardes, Jeanne; Gely-Nargeot, Marie-Christine; Capdevielle, Delphine; Van der Linden, Martial
Abstract : The ability to project oneself into the future contributes to development and maintenance of a coherent sense of identity. If recent research has revealed that schizophrenia is associated with difficulties envisioning the future, little is known about patients' future self-representations. In this study, 27 participants with schizophrenia and 26 healthy controls were asked to simulate mental representations of plausible and highly significant future events (self-defining future projections, SDFPs) that they anticipate to happen in their personal future. Main results showed that schizophrenia patients had difficulties in reflecting on the broader meaning and implications of imagined future events. In addition, and contrary to our hypothesis, a large majority of SDFPs in schizophrenia patients were positive events, including achievements, relationship, and leisure contents. Interestingly, patients and controls did not differ on the perceived probability that these events will occur in the future. Our results suggest that schizophrenia patients have an exaggerated positive perception of their future selves. Together, these findings lend support to the idea that past and future self-defining representations have both similar and distinct characteristics in schizophrenia.